2014
DOI: 10.1007/s00148-014-0532-x
|View full text |Cite
|
Sign up to set email alerts
|

Can’t buy mommy’s love? Universal childcare and children’s long-term cognitive development

Abstract: What happens to children's long-run cognitive development when introducing universal high-quality childcare for 3-year-olds mainly crowds out family care? To answer this question, we take advantage of a sizeable expansion of publicly subsidized full-time high-quality childcare for 3-year-olds in Spain in the early 1990s. Identification relies on variation in the initial speed of the expansion of childcare slots across states. Using a difference-in-difference approach, we find strong evidence for sizeable impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
109
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(125 citation statements)
references
References 39 publications
8
109
0
8
Order By: Relevance
“…(p. 101). Felfe et al (2015) reach the same conclusion using data from a similar expansion that took place in Spain during the early 1990s. Dustmann et al (2013) exploit a reform that entitled all German preschoolers to a childcare slot.…”
Section: Previous Researchsupporting
confidence: 64%
“…(p. 101). Felfe et al (2015) reach the same conclusion using data from a similar expansion that took place in Spain during the early 1990s. Dustmann et al (2013) exploit a reform that entitled all German preschoolers to a childcare slot.…”
Section: Previous Researchsupporting
confidence: 64%
“…The benefits were found to be large enough to close the scholastic achievement gap between children of high and low socio-economic status, and of native-born and immigrant parents. Felfe et al (2015) evaluated the long-run effects of a policy (implemented in the late 1990s) that introduced universal childcare for 3-year-old children in Spain. They compared the later cognitive outcomes of children who attended childcare with those of previous cohorts, and found a sizable increase in reading and math test scores, and a sizable decrease in the likelihood of falling behind a grade.…”
Section: Previous Studies On the Role Of Early Childcarementioning
confidence: 99%
“…In Spain, a study of the expansion of high-quality preschool for three year olds in the early 1990s showed that preschool reduces grade retention in primary school and improves children's reading skills at age 15 [6]. The effects are largest for disadvantaged children and for girls.…”
Section: Medium-term Studies Following Children Into Their School Yearsmentioning
confidence: 99%